2013
DOI: 10.1177/1748006x13475412
|View full text |Cite
|
Sign up to set email alerts
|

Technique for optimal placement of transducers for fault detection in rotating machines

Abstract: Online fault detection and diagnosis of rotating machinery requires a number of transducers which can be significantly expensive for industrial processes. The sensitivity of various transducers and their appropriate positioning are dependent on different types of fault conditions. It is critical to formulate a method to systematically determine the effectiveness of transducer locations for monitoring the condition of a machine. In this paper, Number of Independent Sources analysis is used as an effective tool … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 26 publications
1
4
0
Order By: Relevance
“…The rate of increase in temperature at the bearings due to frictional heat generation can be determined by solving equation (7). However, for simplicity, assuming a one-dimensional heat transfer model using the lumped parameter approach, the transient time constants of the couplings and bearings were calculated based on equation (11) and are given in Table 3, which is close to some of the experimental observations in this study.…”
Section: Estimation Of Time Constantsupporting
confidence: 63%
See 1 more Smart Citation
“…The rate of increase in temperature at the bearings due to frictional heat generation can be determined by solving equation (7). However, for simplicity, assuming a one-dimensional heat transfer model using the lumped parameter approach, the transient time constants of the couplings and bearings were calculated based on equation (11) and are given in Table 3, which is close to some of the experimental observations in this study.…”
Section: Estimation Of Time Constantsupporting
confidence: 63%
“…In order to detect misalignment, well-established fault detection techniques using vibration spectra at the bearing locations exist. [5][6][7] The vibration measurements at bearing locations are usually done by piezo-electric accelerometers, though recently researchers have also used laser vibrometer to measure the bearing locations from remote locations. Some other techniques that are well developed for condition monitoring are the techniques of motor current signature analysis (MCSA), ultrasonic, radiography and so on.…”
Section: Introductionmentioning
confidence: 99%
“…It was also used to detect imbalance using piezoelectric strain sensors [29]. The misaligned and cracked shaft was also analyzed on this simulator, and sensitive locations for transducers were discussed [30]. This study focuses on multiple damages in roller bearings; bearing damages have been analyzed by comparing the intact bearing's histogram and kurtosis values with the following defected bearings: (1) inner race defect; (2) outer race defect; (3) ball defect; and (4) combination defect.…”
Section: Methodsmentioning
confidence: 99%
“…26 The experiments were performed on MFS for angular and parallel misalignments and breathing crack by obtaining vibration data on different speeds to study sensitive location for transducer. 27 In this research, both experiments A and B have been performed to obtain vibration spectra of misaligned shaft for different operational conditions. The experiment C is performed to detect slit and V-notch crack in shaft.…”
Section: Order Analysismentioning
confidence: 99%
“…Vibration spectrum analysis was performed on experimental data obtained from MFS to illustrate the proposed selection process. 27 The literature concluded that the vibration spectrum is a widely used method for detecting the real-world faults in rotating machinery, and a lot of gaps are present that can be addressed by analysing the effects of shaft misalignment and cracked shaft in rotating machinery with order analysis, so that it can help in implementation of industry 4.0. In this research article, the use of order analysis to detect shaft misalignment and cracked shaft is explored.…”
Section: Introductionmentioning
confidence: 99%